Visual Aesthetic Experience and Emotion Regulation among Millennials in City of Imus - Jervin Dinglasan Quicho; Rogemar F. Dela Cruz; Lyka Ueric C. Delos Santos; John Paulo O. Matibag (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study examined the relationship between visual aesthetic experience and emotion regulation among 139 millennial residents (aged 29-44) in City of  Imus, Cavite. Using a descriptive-correlational design, participants completed the Aesthetic Experience Questionnaire (AEQ) measuring emotional, cultural, perceptual, understanding, flow-proximal conditions, and flow-experience domains, and the Emotion Regulation Questionnaire (ERQ) assessing cognitive reappraisal and expressive suppression. Results revealed that most respondents exhibited low levels of overall visual aesthetic experience (53.2%) and low emotion regulation in both cognitive reappraisal (52.5%) and expressive suppression (54.7%). Spearman Rho correlation analysis demonstrated significant positive relationships between overall aesthetic experience and both cognitive reappraisal (r = 0.461, p < 0.001) and expressive suppression (r = 0.283, p < 0.001), indicating that deeper engagement with visual art corresponds to enhanced emotion regulation capabilities. The cultural domain showed the strongest correlation with cognitive reappraisal (r = 0.487, p < 0.001), while flow-proximal conditions correlated most strongly with expressive suppression (r = 0.326, p < 0.001). Based on these findings, the researchers developed "Artful Awareness," a program designed to transform passive art viewing into intentional emotional practice through structured activities including Emotion Landscape Mapping, Inner Voice Portrait, and Emotion Regulation Grid, Art Engagement, and Mark Your Emotions exercises. This module aims to enhance both aesthetic sensitivity and adaptive emotion regulation strategies among millennials in community settings.